Limited Health Literacy Is Associated With Worse Patient-Reported Outcomes in Inflammatory Bowel Disease. Issue 1 (10th July 2018) - Tormey, Lauren K; Reich, Jason; Chen, Yu Sarah; Singh, Arush; Lipkin-Moore, Zachary; Yu, Anzhu; Weinberg, Janice; Farraye, Francis A; Paasche-Orlow, Michael K
Abstract: Background: Patients with inflammatory bowel disease (IBD) face complex health tasks and decisions. Limited health literacy is a risk factor for poor health outcomes, but this has not been examined in IBD. This study aims to assess the role of health literacy for patients with IBD. Methods: We prospectively enrolled adults with IBD receiving care from the Section of Gastroenterology at the Boston Medical Center. In-person, standardized questionnaires were administered to measure health literacy with the Newest Vital Sign, self-efficacy with the Medication Use and Self-Efficacy Scale, quality of life with the 10-question Short Inflammatory Bowel Disease Questionnaire, depression with the Patient-Reported Outcomes Measurement System Short Form, and clinical disease activity for patients with Crohn's disease with the Harvey-Bradshaw Index and for patients with ulcerative colitis with the Simple Clinical Colitis Activity Index (SCCAI). The relationships between health literacy and these variables were subsequently examined. Results: Of 112 patients invited to participate, 99 enrolled and completed the interview. Limited health literacy was identified in 40% (n = 40) of patients. Patients with limited health literacy reported significantly worse overall health ( P = 0.03) and more depressive symptoms ( P = 0.01). Of the 56 patients with Crohn's disease, those with adequate health literacy were more likely to be in clinical remission (mean Harvey-Bradshaw Index score < 5), compared with those with limited health literacy (odds ratio, 4.15; 95% confidence interval, 1.37 to 13.45; P = 0.01). There was no significant association between health literacy and clinical disease activity (SCCAI) in patients with ulcerative colitis. Conclusions: Limited health literacy is associated with lower ratings of subjective health and depression in IBD and more symptoms of active disease in patients with Crohn's disease.